Peran Guru Dalam Membangun Moderasi Beragama di Sekolah - Hafizh Idri Purbajati (FALASIFA : Jurnal Studi Keislaman, 2020)
Indonesia is a nation consisting of thousands of islands, various races, ethnicities, languages, tribes, and cultures. This shows that Indonesia is a country rich in diversity. The threat of conflict becomes even greater. There are actions that lead to radicalism, extremism, hatred of certain parties, violence, and vandalism can be a factor in destroying unity. Therefore, religious moderation is very important to be applied in the life of the nation and state. Internalization of religious moderation is important to be applied from an early age in the school environment. It aims to instill strongly so that students can understand and practice the values ​​of religious moderation in the school and community environment. Teachers have a very important role in making this happen. This is because the teacher is the party who is in direct contact with the students. This article will discuss the role of teachers in efforts to build religious moderation in schools.